Comparative studies on the processing and performance of carbon nanotube and nanofibre based multi-scale composites - Rana, S. (2014)
The present research compares the processing and various properties of carbon/epoxy multiscale composites developed incorporating vapor-grown carbon nanofibres (VCNFs) and single-walled carbon nanotubes (SWCNTs). CNFs and SWCNTs (0.5-1.5 wt. %) were dispersed within epoxy resin using a combination of ultrasonication and mechanical stirring in the presence of a non-ionic surfactant and the nanomaterial/resin dispersions were used to impregnate carbon fabrics in order to develop multi-scale composites. It was observed from the experimental results that SWCNTs needed much longer dispersion treatment as compared to CNFs; however, the improvement in properties in case of CNT based multi-scale composites was also much higher. Incorporation of up to 1.5 wt.% of CNT within carbon/epoxy composites led to improvements of 46% in elastic modulus, 9% in tensile strength, 150% in breaking strain, 170% in toughness, 95% in storage modulus (at 25°C), 167% in thermal conductivity and also significant improvements in the wear performance of composites. Additionally, the modeling approach showed that the multi-scale composites, especially containing SWCNTs, presented elastic modulus very close to the predicted values.